Prevalence of sheep toxoplasmosis in two regions in Puno, Peru - Bernal M., Dapne (2015)
The aim of this study was to determine the seroprevalence ofToxoplasma gondii in two regions of the province of Lampa, in Puno, Peru. A total of 100 blood samples were collected from sheep of various ages and were analyzed by the indirect immunofluorescent assay (IFA). The seroprevalence was 44%. Sex was not considered a risk factor, but the frequency of positive cases increased with age (p<0.05).